(untitled) (South Asian Journal of Agriculture, 2022)
Drought stress affects plant growth and development and ultimately reduces the grain yield of rice. The use of periodical water stress and potassium fertilization may enhance rice tolerance to drought stress. But drought at different growth stages may respond differently which is still unclear. This research work was carried out to determine the effects of different periodical water stress combined with potassium fertilization on growth, yield, leaf gas exchanges and biochemical changes in transplanted Aman rice (cv. BRRI dhan71) grown in the field condition and compare them with standard practice (control). Three levels of water stress (Control: Regular irrigation with 1 cm standing water, periodical water stress for 10 days from 15 days after transplanting (DAT) to harvest and water stress for 10 days after panicle initiation or reproductive phase) and two potassium (K) fertilization levels (41 kg K ha-1 and 51 kg K ha-1) were evaluated in this experiment. The application of water stress for 10 days at the reproductive phase and application of potassium at 51 kg K ha-1 showed tolerance to drought stress by increasing chlorophyll content, proline levels and maximum efficiency of photosynthesis in comparison to other treatments. It was observed that rice yield and other physiological parameters reduced with increasing duration of water stress by periodical water stress for 10 days from 15 DAT to maturity while application of additional potassium fertilizer (51 kg K ha-1) has a slight effect on those parameters. From our observation, 10 days of water stress at the reproductive phase of rice with potassium fertilization at 51 kg K ha−1 produced higher grain yield and yield components that are equivalent to standard practice. It was also observed that the biomass and filled spikelet were not affected by without irrigation for 10 days at reproductive phase. Therefore, it could be stated that the rice variety BRRI dhan71 does not require flood irrigation and water stress for 10 days at the reproductive phase is more appropriate to increase water use and optimum yield of rice. South Asian J. Agric., 8(1&2): 36-44